AMPA receptors mediate the pro-cognitive effects of electrical and optogenetic stimulation of the medial prefrontal cortex in antidepressant non-responsive Wistar–Kyoto rats - Papp, Mariusz (J Psychopharmacol, 2020)
BACKGROUND: The chronic mild stress (CMS) procedure is a widely used animal model of depression, and its application in Wistar–Kyoto (WKY) rats has been validated as a model of antidepressant-refractory depression. While not responding to chronic treatment with antidepressant drugs, WKY rats do respond to acute deep brain stimulation (DBS) of the medial prefrontal cortex (mPFC). In antidepressant-responsive strains there is evidence suggesting a role for AMPA subtype of glutamate receptor in the action mechanism of both antidepressants and DBS. METHODS: Animals were subjected to CMS for 6 to 8 weeks; sucrose intake was monitored weekly and novel object recognition (NOR) test was conducted following recovery from CMS. Wistars were treated chronically with venlafaxine (VEN), while WKY were treated acutely with either DBS, optogenetic stimulation (OGS) of virally-transduced (AAV5-hSyn-ChR2-EYFP) mPFC or ventral hippocampus, or acute intra-mPFC injection of the AMPA receptor positive allosteric modulator CX-516. The AMPA receptor antagonist NBQX was administered, at identical sites in mPFC, immediately following the exposure trial in the NOR. RESULTS: Sucrose intake and NOR were suppressed by CMS, and restored by VEN in Wistars and by DBS, OGS, or CX-516 in WKY. However, OGS of the ventral hippocampal afferents to mPFC was ineffective. A low dose of NBQX selectively blocked the procognitive effect of VEN, DBS and OGS. CONCLUSIONS: These results suggest that activation of AMPA receptors in the mPFC represents a common pathway for the antidepressant effects of both conventional (VEN) and novel (DBS, OGS) antidepressant modalities, in both antidepressant responsive (Wistar) and antidepressant-resistant (WKY) rats.